Correlation of the CT Scan Findings and Neurologic Impairment in Thoracolumbar Burst Fractures - Sharma, Umesh Kumar; Thapa, Dinesh Kumar; Thapaliya, Suraj; Pokhrel, Abishek; Shrestha, Man Mohan Bir; Nepal, Pankaj Raj; Parajuli, Nirajan Prasad (Eastern Green Neurosurgery, 2020)
Background: Spinal injury is the most common injury which may lead to devastating disability. Such fractures are relatively rare but frequently result in neurologic damage due in part to retro- pulsed fragments that narrow the spinal canal. Hereby we would like to correlate the CT scan findings and neurologic impairment in thoracolumbar burst fractures at our center. Materials and Methods: This prospective observational study was conducted at B&C teaching hospital, Birtamode, Nepal. Patients were evaluated by CT scan between July 2016 to December 2018 referred from the emergency department with a history of trauma and suspected thoracolumbar vertebral fractures with or without neurological deficit were included in the study. The different demographic variables like gender, age were included and injury at the level of the spine and neurological deficit was studied. Thus, obtained data were processed in statistical software and expressed in percentage and frequency. Results: The total number of patients was 34 (male: 19, female: 15). The age ranged from 16 years to 77 years with a mean age of 39.1 years. The neurologic deficit was detected in 10 cases (29.4%), out of which complete deficit in 6 (60%) and incomplete deficit in 4 (40%). The neurologic deficit was absent in 24 cases (70.6%). An associated laminar fracture was detected in 17 patients (50%). Laminar fracture associated with the neurologic deficit was found in 10 patients. Conclusion: CT scan is an excellent imaging modality for the evaluation of thoracolumbar fractures. Measurement of central canal ratio and assessment of associated laminar fracture can be useful information to predict the neurologic deficit and plan for further management.